2014
DOI: 10.1007/s13197-014-1641-y
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and functional characterization of barley flaxseed based functional dry soup mix

Abstract: Barley flaxseed based functional dry soup mix (BFSM) was developed from whole barely flour (46.296%), roasted flaxseed powder (23.148%) and the seasoning (30.555%) comprising several flavoring compounds and anticaking agent, using simple processing technique. Developed BFSM was nutritious. On dry matter basis it contained: protein (14.31%), carbohydrate excluding crude fiber (54.70%), fat (8.70%), ash (17.45%) and crude fiber (4.84%). It was low glycemic soup, free of antinutritional risk and had calorific val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Rao et al (2011) prepared an Indian traditional product (chutney powder) containing 50% flaxseed powder and reported that the total phenol content of functional food adjunct increased with addition of flaxseed powder. Also, another researcher (Kaur and Das, 2014) reported similar observations of increases in phytochemical properties (total phenol content and antioxidant) with the incorporation of flaxseed in functional dry soup mix.…”
Section: Phytochemical Propertiesmentioning
confidence: 58%
“…Rao et al (2011) prepared an Indian traditional product (chutney powder) containing 50% flaxseed powder and reported that the total phenol content of functional food adjunct increased with addition of flaxseed powder. Also, another researcher (Kaur and Das, 2014) reported similar observations of increases in phytochemical properties (total phenol content and antioxidant) with the incorporation of flaxseed in functional dry soup mix.…”
Section: Phytochemical Propertiesmentioning
confidence: 58%
“…The data was subjected to the appropriate statistical analysis using SPSS (version, 16) [28]. The analysis of variance (one way ANOVA) and Spearman's correlation coefficient were determined to evaluate the best developed test product.…”
Section: Discussionmentioning
confidence: 99%
“…The food products namely, flaxseed chutney [11], flaxseed chutney powder [12], peanut chikki incorporated with flaxseeds [13], flaxseed cookies [14], flaxseed energy bar [15], flaxseed soup mix [16], have been prepared owing to numerous health incentives and physiological wellness on flaxseed consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The GI scale varies from 1 to 100. Based on this, foods are categorized into three groups, that is, high GI foods (GI ≥70, rapid rise in blood glucose levels), intermediate GI foods (56 ≤ GI ≤69, medium rise in Whole jamun based functional confection; # mean ± SD with n = 3; * difference between mean is non-significant (p > 0.05) blood glucose level) and low GI foods (GI ≤55, slow rise in blood glucose level) (Kaur and Das 2015).…”
Section: Glycemic Indexmentioning
confidence: 99%